Preclinical type 1 diabetes mellitus: a case from practice - Yu. G. Samoilova; T. A. Filippova; M. V. Koshmeleva; O. A. Oleynik; E. V. Gorbatenko (Лечащий Врач)
At the preclinical stage diabetes mellitus can be diagnosed based on laboratory studies of blood glucose and detection of autoantibodies to insulin (IAA), islet cells (ICA), glutamate decarboxylase (GADA), tyrosine phosphatase (IA2A) and zinc transporter (ZnT8A). This article describes a case of preclinical type 1 diabetes mellitus with positive seroconversion to several types of autoantibodies. This suggests a clinical manifestation of type 1 diabetes mellitus in the forthcoming years.